New Cad Model of the Microstrip Interdigital Capacitor - Nihad Dib; Qiu Zhangb; Ulrich Rohde (Active and Passive Electronic Components)
A new model for the microstrip line interdigital capacitor is proposed. This model consists of calculating the 2N×2N Y-matrix of the N coupled lines using the multiple coupled line tool. Then, this matrix is reduced to a 2×2 matrix using simple circuit theory. The capacitance at the end of each finger is taken into consideration using closed-form expression of the coplanar waveguide open-end capacitance. This model can predict the resonances that might appear around the quarter-wavelength frequency. These resonances are caused by the coupling between the fingers and exist only in capacitors with four fingers or more. Very good agreement is obtained between the results of our model and those obtained using the software HFSS and measurements.